1976
DOI: 10.1093/nar/3.10.2633
|View full text |Cite
|
Sign up to set email alerts
|

Nuclease digestion in between and within nucleosomes

Abstract: In the course of digestions of rat liver nuclei with micrococcal nuclease the size of the nucleosomal DNA is shortened by 50-60 nucleotide pairs from starting lengths of about 200, 400, 600, 800, etc. nucleotide pairs in the monomeric and oligomeric nucleosomes, respectively. Acid soluble DNA material is created relatively slowly as compared to the rate of formation of subnucleosomal material. More DNA with lengths in between the 200, 400, etc. nucleotide pairs of nucleosomal DNA is formed when digestions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…In agreement with [6,7] our results indicate that DNase II initially cleaves erythrocyte nuclear DNA at 210 bp intervals ( fig.lB) and that, as digestion proceeds, the 100 bp periodicity of DNA fragmentation is revealed ( fig. 1C).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with [6,7] our results indicate that DNase II initially cleaves erythrocyte nuclear DNA at 210 bp intervals ( fig.lB) and that, as digestion proceeds, the 100 bp periodicity of DNA fragmentation is revealed ( fig. 1C).…”
Section: Resultssupporting
confidence: 92%
“…To analyze the mechanism of dinucleosomal periodicity of chromatin fragmentation we used DNase II -a nuclease which is able to cleave chromatin not only in the linker DNA region (just like micrococcal nuclease), but also within nucleosome core giving rise to a 100 bp repeat [5][6][7]. We have demonstrated that formation of a double-nucleosome repeat generated by DNase II is the result of DNA cleavage at the sites identified within nucleosome core [7].…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that the 'double nucleosome' and the 'half nucleosome' repeat patterns have a common origin determined by the higher order structure of chromatin and not by the mode of digestion of the nucleases. Indeed when nuclei were digested with micrococcal nuclease at O"C, two distinct shoulders were seen between mono-and dinucleosome peaks with lengths of 260 and 320 bp [18] corresponding to N + 50 and to 2N-1OOn.…”
Section: Abbreviationsmentioning
confidence: 99%
“…The chromatin structure is classically probed with nucleases (61). The endonuclease micrococcal nuclease (MCN), for example, preferentially cleaves linker DNA between nucleosomes (2,19). Mild MCN digestions first cleave linker DNA sparsely, releasing polynucleosomes, which are eventually cleaved to mononucleosomes.…”
mentioning
confidence: 99%